PENGARUH LIKUDITAS DAN FAKTOR LAIN TERHADAP CASH HOLDING DI MODERASI GOOD CORPORATE GOVERNANCE - Ng, Michelle; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The purpose of this study was to obtain evidence related to the effect of liquidity, leverage, company size, capital expenditure, and good corporate governance on cash holdings in manufacturing companies listed on the Indonesia Stock Exchange during the period 2018 to 2020. With purposive sampling technique, the data used in this study as many as 52 companies with a total 156 observations of data for three years and processed using the Eviews 12 software. This study uses Multiple Regression Analysis and Moderated Regression Analysis. The results of the study partially show that liquidity and capital expenditure do not have a significant effect on cash holding. Meanwhile, leverage and company size have a significant effect on cash holding. Good corporate governance as a moderating variable to examine the relationship between capital expenditure and cash holding shows that good corporate governance does not moderate the relationship between capital expenditure and cash holding.